2010
DOI: 10.1158/1535-7163.mct-10-0368
|View full text |Cite
|
Sign up to set email alerts
|

Monensin Is a Potent Inducer of Oxidative Stress and Inhibitor of Androgen Signaling Leading to Apoptosis in Prostate Cancer Cells

Abstract: Current treatment options for advanced and hormone refractory prostate cancer are limited and responses to commonly used androgen pathway inhibitors are often unsatisfactory. Our recent results indicated that sodium ionophore monensin is one of the most potent and cancer-specific inhibitors in a systematic sensitivity testing of most known drugs and drug-like molecules in a panel of prostate cancer cell models. Because monensin has been extensively used in veterinary applications to build muscle mass in cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 56 publications
(60 reference statements)
12
84
1
3
Order By: Relevance
“…Monensin antibacterial and antiparasitic activity is related to the intracellular changes in pH and sodium-potassium balance that can result in cell death (40). Several recent studies have demonstrated that monensin inhibits growth and induces apoptosis of cells derived from renal, prostate, and colon carcinoma (29,41,42). In addition, monensin induced cell-cycle arrest of acute myelogenous leukemia and lymphoma cells (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monensin antibacterial and antiparasitic activity is related to the intracellular changes in pH and sodium-potassium balance that can result in cell death (40). Several recent studies have demonstrated that monensin inhibits growth and induces apoptosis of cells derived from renal, prostate, and colon carcinoma (29,41,42). In addition, monensin induced cell-cycle arrest of acute myelogenous leukemia and lymphoma cells (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…4G). In prostate cancer cells, monensin treatment reduced the amount of androgen receptor mRNA and elevated oxidative stress (29). However, monensin did not increase the levels of reactive oxygen species (ROS) in HEK293 and SW480 cells ( Supplementary Fig.…”
Section: Monensin Attenuates Aberrant Wnt Signaling In Human Colorectmentioning
confidence: 99%
“…Only four compounds, antibiotic ionophore monensin, aldehyde dehydrogenase (ALDH) inhibitor disulfiram, histone deacetylase inhibitor trichostatin A and fungicide thiram inhibited selectively cancer cell growth at nanomolar concentrations. The mechanistic studies indicated that monensin and disulfiram inhibited prostate cancer cell growth by inducing oxidative stress (Iljin et al 2009, Ketola et al 2010. In contrast to disulfiram, monensin induced apoptosis, reduced androgen receptor signalling and showed a synergistic anti-proliferative effect with anti-androgens in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…androgen receptor (AR), ERG and MYC are known to have antioxidative properties in cancer cells (Pinthus et al 2007, Tam et al 2003, Benassi et al 2006, Swanson et al 2011, DeNicola et al 2011. Monensin may sensitize prostate cancer cells to oxidative stress via reducing the expression of these genes (Ketola et al 2010). In addition, many other anti-neoplastic agents such as vinblastine, cisplatin, mitomycin C, doxorubicin, camptothecin, inostamycin, neocarzinostatin, etoposide, arsenic trioxide and nonsteroidal anti-inflammatory drugs are known to mediate their apoptotic effect by inducing oxidative stress (Fang, Nakamura & Iyer 2007, Rigas, Sun 2008, Sun et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation